2017
DOI: 10.1096/fj.201700126r
|View full text |Cite
|
Sign up to set email alerts
|

Unacylated ghrelin normalizes skeletal muscle oxidative stress and prevents muscle catabolism by enhancing tissue mitophagy in experimental chronic kidney disease

Abstract: Unacylated ghrelin (UnAG) may lower skeletal muscle oxidative stress, inflammation, and insulin resistance in lean and obese rodents. UnAG-induced autophagy activation may contribute to these effects, likely involving removal of dysfunctional mitochondria (mitophagy) and redox state maintenance. In chronic kidney disease (CKD) oxidative stress, inflammation and insulin resistance may negatively influence patient outcome by worsening nutritional state through muscle mass loss. Here we show in a 5/6 nephrectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 51 publications
4
61
0
Order By: Relevance
“…C2C12 myoblasts were differentiated in myotubes as previously reported . After 4 day incubation periods with differentiation medium and 18 h starvation, they were treated with AG (0.1 or 1 μmol/L) for 48 h, followed by collection and processing.…”
Section: Methodsmentioning
confidence: 99%
“…C2C12 myoblasts were differentiated in myotubes as previously reported . After 4 day incubation periods with differentiation medium and 18 h starvation, they were treated with AG (0.1 or 1 μmol/L) for 48 h, followed by collection and processing.…”
Section: Methodsmentioning
confidence: 99%
“…A 5/6 nephrectomy was chosen as the model of renal disease [ 14 ]. Animals were randomly assigned to receive single-step laparotomic 5/6 nephrectomy or sham operation as recently described by the authors of [ 15 ]. After anaesthesia (premedication: Dexmedetomidine 0.05 mg/kg IP, anaesthesia: Zoletil 25 mg/kg IP, lidocaine 4 mg/kg local infiltration), median laparotomy, opening of the retro-peritoneum and left kidney isolation, the renal artery was clamped and the inferior and superior poles were resected.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a study employing a murine model of sepsis induced by cecal ligation and perforation showed that limb muscles exhibit higher autophagy than do respiratory muscles [ 188 ]. Another recent study using an experimental model of CKD revealed a correlation between skeletal muscle oxidative stress, muscle catabolism, and autophagy, finding that inhibition of oxidative stress could improve muscle atrophy by enhancing mitophagy [ 189 ]. Moreover, a C26 cell-induced cancer model demonstrated that exercise increased autophagy flux, improving muscle homeostasis, probably due to the removal of damaged proteins and mitochondria [ 190 ].…”
Section: Redox Regulation Of Molecular Mechanisms Of Cachexiamentioning
confidence: 99%